Effect of different extenders, cryoprotectanys, equilibration and vapour exposure on freezability of African catfish (clarias gariepinus) sperm - Noor Azlina Kamaruding (Universiti Malaya, 2012)
The aim of this study was to develop an optimal freezing protocol for African catfish sperm with special reference to type of extender and cryoprotectant.